INSTABILITY OF COASTAL LOWLANDS DUE TO SEISMIC ACTIVITIES - H. B. Poorooshasb (Lowland Technology International, 2003)
In certain regions of the world the coastal lowlands consist of a two to three meters of impervious material supported by a layer of sand and underlain by a thick layer of stiff marine clay. One such region is in the vicinity of the City of Bushire (Bushehr) located in the northern shores of the Persian Gulf. Here the top layer is a two to three meter thick coquina layer, resting on a very loose sand deposit of almost constant thickness (about 50-60 cm) having a gentle slope of about 5-10 degrees towards the sea. A sever earthquake in this region several centuries ago completely destroyed the City of Siraf which, at the time, was the most important port of the Persian Gulf on the Silk Route. The present paper presents an analysis of the situation using the CANAsand Constitutive Model and the ID technique proposed by the Author and his Colleagues at Institute of Lowland Technology, Saga University, Poorooshasb et al (1996).